Cognitive impairments and neuronal injury in different brain regions of a genetic rat model of absence epilepsy. (9th July 2015) - Jafarian, M.; Karimzadeh, F.; Alipour, F.; Attari, F.; Lotfinia, A.A.; Speckmann, E.-J.; Zarrindast, M.-R.; Gorji, A.
Highlights: Cognitive deficits are part of clinical profile of childhood absence epilepsy. Cognitive deficits have also been reported in animal models of absence epilepsy. Cognitive functions and cell injury/death in the brain of WAG/Rij rats were studied. Cognitive deficits were accompanied by a higher cell injury/death in WAG/Rij rats. Seizure-induced cell injury/death may underlie cognitive deficits in absence epilepsy. Abstract: Growing numbers of evidence indicate that cognitive impairments are part of clinical profile of childhood absence epilepsy. Little is known on neuropathological changes accompanied by cognitive deficits in absence epilepsy. The aim of the present study was to investigate age-dependent neuropathological changes accompanied by learning and memory impairments in Wistar Albino Glaxo from Rijswijk (WAG/Rij) rat model of absence epilepsy. Experimental groups were divided into four groups of six rats of both WAG/Rij and Wistar strains with 2 and 6 months of age. The learning and memory performances were assessed using passive avoidance paradigm and neuropathological alterations were investigated by the evaluation of the number of dark neurons and apoptotic cells as well as the expression of caspase-3 in the neocortex, the hippocampus, and different regions of the thalamus. Results revealed a decline in learning and spatial memory of 6-month-old WAG/Rij rats compared to age-matched Wistar rats as well as 2-month-old WAG/Rij and Wistar rats. The mean number of dark neurons was significantly higher in the hippocampal CA1 and CA3 areas as well as in the laterodorsal, centromedial, and reticular thalamic nuclei and the somatosensory cortex of 6-month-old WAG/Rij rats. In addition, a higher number of apoptotic cells as well as a higher expression of caspase-3 was observed in the hippocampal CA1 and CA3 regions, the laterodorsal thalamic nucleus, and the somatosensory cortex of 6-month-old WAG/Rij rats compared to other animal groups. These results indicate significant enhancement of neuronal damage and cell death accompanied by memory deficits after seizure attacks in a rat model of absence epilepsy. Seizure-induced neuronal injury and death may underlie cognitive impairments in absence epilepsy.